Mubtada’ and Khobar in the Arabic Sentence Formation in the Nahwu Basic Theory Book - Ghofur, M Abdul; bin Nafsah, Nor Holis; Abdul Jalil Mannan, Ahmad Mizan Rosyadi; Mubarok, Achmad Hadi (UAS PRESS, 2026)
In everyday life, humans cannot be separated from the use of language as a means of communication. However, not many people realize that even a simple sentence structure, such as